2002
DOI: 10.1103/physrevb.65.174524
|View full text |Cite
|
Sign up to set email alerts
|

Incommensurate dynamics of resonant breathers in Josephson junction ladders

Abstract: We present theoretical and experimental studies of resonant localized resistive states in a Josephson junction ladder. These complex breather states are obtained by tuning the breather frequency into the upper band of linear electromagnetic oscillations of the ladder. Their prominent feature is the appearance of resonant steps in the current-voltage (I-V ) characteristics. We have found the resonant breather-like states displaying incommensurate dynamics. Numerical simulations show that these incommensurate re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…This has been achieved both theoretically and experimentally by using the fact that when driving a breather into a resonance, not all resistive junctions have to lock to to the cavity mode [109]. In such a case the breather becomes an object, where different resistive junctions rotate at different incommensurate frequencies.…”
Section: Resonances With Cavity Modesmentioning
confidence: 98%
“…This has been achieved both theoretically and experimentally by using the fact that when driving a breather into a resonance, not all resistive junctions have to lock to to the cavity mode [109]. In such a case the breather becomes an object, where different resistive junctions rotate at different incommensurate frequencies.…”
Section: Resonances With Cavity Modesmentioning
confidence: 98%
“…The theoretical prediction for the positions of the resonances was also compared with numerical simulations. In a different work Fistul et al 15 studied the quasiperiodic dynamics found in some of the resonant breathers experimentally found in arrays with ϭ2.6 and ⌫ϭ0.025.…”
Section: New Experiments Analysis and Simulationsmentioning
confidence: 98%
“…After these works more experiments were done and the results reported on various publications. [12][13][14][15][16][17] Experiments at MIT 2 were done in open ladders with nine vertical junctions ͑see Fig. 6͒.…”
Section: The Experimental Detectionmentioning
confidence: 99%
“…This has been achieved, both theoretically and experimentally, by using the fact that not all resistive junctions have to lock to the cavity mode when a breather is driven into a resonance [40]. In such a case, the breather becomes an object where different resistive junctions rotate at various incommensurate frequencies.…”
Section: Roto-breather Solutions and Their Current-voltage Dependenciesmentioning
confidence: 99%